2015
DOI: 10.1007/s12185-015-1843-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the molecular mechanism underlying bone marrow necrosis with acute lymphoblastic leukemia

Abstract: Bone marrow necrosis (BMN) is a rare phenomenon in children with malignancies, occurring most commonly in patients with acute lymphoblastic leukemia (ALL). The pathophysiology of this phenomenon has not been identified. We analyzed seven BMN cases with ALL in order to elucidate the underlying mechanism. Serum high-mobility group box 1 (HMGB1), cytochrome C, cytokines, and chemokines were measured, and real-time quantitative reverse transcription-polymerase chain reaction (RQ-RT-PCR) and immunochemistry of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…One month later, leukemia cells appeared in the peripheral blood, leading to a diagnosis of ALL. In addition, Moritake et al showed that leukemic cell-eliciting Fasligand and macrophage-eliciting tumor necrosis factor-alpha could be associated with the molecular mechanism underlying BMN with ALL (19). Thus, because these cytokines from leukemic cells can cause BMN, reducing the tumor burden via chemotherapy, as was reported by Miyoshi et al, could be effective for relieving BMN and may be useful for making a reliable disease assessment.…”
Section: Discussionmentioning
confidence: 92%
“…One month later, leukemia cells appeared in the peripheral blood, leading to a diagnosis of ALL. In addition, Moritake et al showed that leukemic cell-eliciting Fasligand and macrophage-eliciting tumor necrosis factor-alpha could be associated with the molecular mechanism underlying BMN with ALL (19). Thus, because these cytokines from leukemic cells can cause BMN, reducing the tumor burden via chemotherapy, as was reported by Miyoshi et al, could be effective for relieving BMN and may be useful for making a reliable disease assessment.…”
Section: Discussionmentioning
confidence: 92%
“…The main clinical features of BMN are as follows: bone pain, a fever, cytopenia, elevated LDH, ALP and ferritin, and leukoerythroblastosis (1). Although BMN in hematologic malignancies seems to be associated with microvascular failure due to hypercellular bone marrow and the extrinsic pathway of apoptosis, its pathophysiology has not been fully elucidated (1,8). In patients with hematologic malignancies with BMN, lymphoid malignancy is dominant over myeloid ma-lignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pglycoprotein expressed by NK cells is reported to be responsible for its refractoriness to chemotherapy [8]. On the other hand, Kawa et al [9] introduced immunosuppressive and cytoreductive therapy with prednisolone, cyclosporine A and etoposide to a case of systemic active EBV infection. However, it did not benefit our case and pancytopenia was progressive even though symptoms fell down.…”
Section: Discussionmentioning
confidence: 99%
“…Although membrane-bound FasL can be converted to a soluble form (sFasL) [1], sFasL is undetectable in the serum of healthy person and that of patients with most subtypes of lymphoma or leukemia. It is contrarily elevated in patients with T-large granular lymphocytic (LGL) leukemia and natural killer (NK) cell lymphoma [2][3][4][5][6], suggesting that Fas-FasL system plays a crucial role in characteristic systemic tissue damage observed in these types of hematological tumor [7][8][9]. We report a case of ANKL accompanied by bone marrow necrosis (BMN) with severe bone pain after granulocyte colony-stimulating factor (G-CSF) administration.…”
Section: Introductionmentioning
confidence: 99%